2017
DOI: 10.1096/fj.201601340rr
|View full text |Cite
|
Sign up to set email alerts
|

Tet1 overexpression leads to anxiety‐like behavior and enhanced fear memoriesviathe activation of calcium‐dependent cascade through Egr1 expression in mice

Abstract: Ten-eleven translocation methylcytosine dioxygenase 1 () initiates DNA demethylation by converting 5-methylcytosine (5-mC) to 5-hydroxymethylcytosine (5-hmC) at CpG-rich regions of genes, which have key roles in adult neurogenesis and memory. In addition, the overexpression of Tet1 with 5-hmC alteration in patients with psychosis has also been reported, for instance in schizophrenia and bipolar disorders. The mechanism underlying Tet1 overexpression in the brain; however, is still elusive. In the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 62 publications
2
22
0
Order By: Relevance
“…In contrast, acute Tet1 FL repression resulted in memory deficits. In line with our results, a recent study showed that transgenic overexpression of the Tet1 FL gene causes enhanced memory formation and increased anxiety in mice (Kwon et al, 2018), suggesting that overexpression of the fulllength enzyme acts oppositely to our SID4X-mediated suppression. It is important to note that while our isoform-specific behavioral findings generally agree with previous reports, several groups have found that pan-Tet1 deficient mice either have normal memory or exhibit an impairment (Zhang et al, 2013;Towers et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, acute Tet1 FL repression resulted in memory deficits. In line with our results, a recent study showed that transgenic overexpression of the Tet1 FL gene causes enhanced memory formation and increased anxiety in mice (Kwon et al, 2018), suggesting that overexpression of the fulllength enzyme acts oppositely to our SID4X-mediated suppression. It is important to note that while our isoform-specific behavioral findings generally agree with previous reports, several groups have found that pan-Tet1 deficient mice either have normal memory or exhibit an impairment (Zhang et al, 2013;Towers et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…For instance, depending on the study, loss of the gene in KO mice has been reported to either impair, enhance, or have no effect, on memory (Rudenko et al, 2013;Zhang et al, 2013;Kumar et al, 2015;Towers et al, 2018). Likewise, overexpression of Tet1 enhances memory, while expression of its catalytic domain does the opposite (Kaas et al, 2013;Kwon et al, 2018). A potential explanation for some of these inconsistences comes from a recent report that the Tet1 gene undergoes an isoform switch from the full-length, canonical transcript (hereafter Tet1 FL ) in embryonic stem cells to a shorter, truncated variant (hereafter Tet1 S ) exclusive to somatic tissues (Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…4c). The activation of 16 EGR1 is involved in peripheral myelin development and adult neurogenesis through oligodendrocyte differentiation via neuron-glia signaling (Kwon et al, 2018;Stevens & Fields, 2000). Therefore, the activation of EGR1 may mediate LCN2-regulated remyelination by inhibiting OPC differentiation.…”
Section: Lcn2 Activates Egr1 In Opcsmentioning
confidence: 99%
“…Intriguingly, converging evidence suggests that psychotic AD (AD + P) [96] is associated with an acceleration of frontal degeneration, with tau pathology playing a primary role [97]. Within this context, a new study by Kwon et al [98] shows that Tet1 over-expression leads to anxiety-like behavior and enhanced fear memories via the activation of calcium-dependent cascade through Egr1 expression in mice.…”
Section: Mirna Regulation Of Taumentioning
confidence: 99%